Influence of 3D Printed Topological Structure on Lightweight Mullite Load Bearing Board in Thermal Environment - Yiran Man; Xudong Luo; Zhipeng Xie; Dianli Qu (Advances in Materials Science and Engineering)
In order to achieve the purpose of resource and energy saving in the process of producing ceramics products, the hollow lightweight load bearing board in thermal environment with topological structures was made by 3D printing. In this study, the load bearing board manufactured with different topological structures such as vertical grid, oblique square grid, and honeycomb grid was printed by direct ink writing technology using the same raw material of kaolin clay and α-Al2O3 powder. The three kinds of samples were sintered at 1450°C × 3 h. The effect of printed structures on mechanical property of load bearing board samples was investigated. Moreover, the finite element simulation was used to study the stress distribution of the load bearing board. Comparing with results obtained by three kinds of samples, honeycomb grid supported samples proved to be the most appropriate structure in various directions comprehensively.